2003
DOI: 10.1177/1082013203034641
|View full text |Cite
|
Sign up to set email alerts
|

New Food Drying Technologies - Use of Ultrasound

Abstract: Reducing water availability is one way to preserve food. Water in solid foods is transferred to a fluid, either gas or liquid; during this process both internal and external resistance affect water transfer from the food. As a consequence, any means to reduce those resistances constitute an improvement of the process, and ultrasound appears to be a way to reduce those resistances. Ultrasound are mechanical waves that produce different effects when travelling through a medium. Among others, those related to mas… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
66
0
6

Year Published

2011
2011
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 170 publications
(74 citation statements)
references
References 26 publications
2
66
0
6
Order By: Relevance
“…These authors showed that the mass transfer was not affected until intensity thresholds were reached (39 and 51 Wcm -2 ) but that above these, the higher the level of ultrasound intensity that was applied, the greater was the effect of ultrasound on mass transport. This effect was also observed with intensity levels as low as 1.3 Wcm -2 at a frequency of 290 kHz (Mulet, Carcel, Sanjuan, & Bon, 2003) Wcm -2 caused a greater loss of meat weight than the control, possibly due to loss of protein.…”
Section: Briningmentioning
confidence: 52%
“…These authors showed that the mass transfer was not affected until intensity thresholds were reached (39 and 51 Wcm -2 ) but that above these, the higher the level of ultrasound intensity that was applied, the greater was the effect of ultrasound on mass transport. This effect was also observed with intensity levels as low as 1.3 Wcm -2 at a frequency of 290 kHz (Mulet, Carcel, Sanjuan, & Bon, 2003) Wcm -2 caused a greater loss of meat weight than the control, possibly due to loss of protein.…”
Section: Briningmentioning
confidence: 52%
“…The continuous alternation of air pressure just above the material's surface triggers turbulence and leads to intensification of heat and mass transfer. Another explanation of this phenomenon can be "sponge effect" which "squeezes out" the moisture from porous material (Cárcel, et al, 2007;Mulet et al, 2003;Simal, et al, 1998).…”
Section: Fig 2 Moisture Ratio (A) and Temperature Curves (B) Obtainmentioning
confidence: 99%
“…Due to its low permeability the barrier to the osmotic solution, both water and substances dissolving in vacuolar sap increases (Kucner et al, 2013). Because of the slowness in solid-liquid mass transfer, several methods have been considered to accelerate the kinetics of this process (Cárcel, et al, 2007;Rastogi et al, 2002), among others the application of pulsed vacuum (Escriche et al, 2000), centrifugal forces (Azuara et al, 1996), electrical fields (Ade-Omowaye et al, 2003;Rastogi et al, 1999) or high intensity ultrasound (Cárcel, et al, 2007;Kowalski and Szadzińska, 2014;Mulet et al, 2003;Siucińska and Konopacka, 2014).…”
Section: Introductionmentioning
confidence: 99%
“…The forces involved by this mechanism can be higher than surface tension which maintains the moisture inside the capillaries and microscopic channels of the fruit, and therefore accelerate moisture removal (Mulet et al, 2003). Ultrasonic waves can reduce viscosity (Greguss, 1963), minimize diffusion boundary layer thickness and remove moisture from solid liquid interfaces (Carcel et al, 2007a;Rodrigues and Fernades, 2007).…”
Section: Introductionmentioning
confidence: 99%